Indigenous Health Practices: A Study of Health-Seeking Behavior of the Lepcha Community in Ilam, Nepal - Karki , Supendra; Adhikari , Indira; karki, Sunira; Aryal , Nishan (International Research Journal of MMC, 2026)
The Lepcha community is an indigenous group residing in the Ilam District of eastern Nepal. Their health-seeking behavior is influenced by cultural beliefs, traditional healing practices, and access to healthcare services. Understanding their healthcare utilization patterns helps identify community health needs and existing barriers. This knowledge is important for developing culturally appropriate and effective health interventions. The primary objective of this study is to examine the relationship between health, culture, and indigenous practices among the Lepcha community in Ward No. 3 of Rong Rural Municipality, Ilam District, Nepal. This study examined health-seeking behavior, health service access, and awareness of non-communicable diseases among the Lepcha community of Rong Rural Municipality–3, Ilam. A descriptive cross-sectional design with census sampling of 42 households was employed. Data were collected through semi-structured interviews and key informant interviews using both quantitative and qualitative methods. The study was conducted over six days, from 2082, using both primary and secondary data sources. The study found that the Lepcha community continues to preserve its cultural identity through traditional festivals, rituals, indigenous knowledge, and strong social values despite the challenges of modernization and population decline. Traditional healing practices and the role of Dhami/Jhakri remain important in health-seeking behavior. At the same time, lifestyle changes have contributed to increasing risks of non-communicable diseases such as hypertension and diabetes. The findings emphasize the need for culturally sensitive health programs and community-based initiatives to improve health outcomes while safeguarding Lepcha cultural heritage. The findings highlight the importance of integrating indigenous health beliefs and practices into formal health programs to improve healthcare utilization among the Lepcha community. Culturally sensitive awareness and education initiatives are essential for strengthening preventive healthcare and promoting informed health-seeking behavior. This study is significant for understanding the indigenous health practices and health-seeking behavior of the Lepcha community, helping to preserve their traditional knowledge and cultural heritage. It also provides valuable evidence for policymakers and healthcare providers to develop culturally sensitive and inclusive public health interventions in Nepal.